2007
DOI: 10.1111/j.1447-0578.2007.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful pregnancy in ovariectomized mice using a combination of heterotopic autotransplantation of ovarian tissues and embryo transfer

Abstract: The present report is the first to show that, after ovariectomy, female mice with autotransplanted ovarian sections can maintain pregnancy after embryo transfer (ET) independent of the transplantation site. Three-month-old ICR females were ovariectomized, and sections from their own ovaries were transplanted either under their kidney capsule (KC group) or into a subcutaneous space (SC group) just after ovariectomy. fertilized blastocysts were transferred into uterine horns of the pseudopregnant mice that had r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Intraperitoneally autografted fresh and vitrified ovarian tissues both contained intact primordial and primary follicles with normal morphology of stromal cells at 5 days after transplantation [11]. Our previous study demonstrated that fresh ovarian tissues that were autotransplanted underneath the kidney capsule and those autotransplanted into the subcutaneous space supported pregnancy and full-term fetal development for transferred embryos [12]. These results indicated that autotransplanted ovarian tissues maintain functional corpora lutea.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Intraperitoneally autografted fresh and vitrified ovarian tissues both contained intact primordial and primary follicles with normal morphology of stromal cells at 5 days after transplantation [11]. Our previous study demonstrated that fresh ovarian tissues that were autotransplanted underneath the kidney capsule and those autotransplanted into the subcutaneous space supported pregnancy and full-term fetal development for transferred embryos [12]. These results indicated that autotransplanted ovarian tissues maintain functional corpora lutea.…”
Section: Introductionmentioning
confidence: 79%
“…Autotransplantation and vitrification of ovarian tissues Autotransplantation was performed as described previously with slight modifications [12]. Briefly, ovaries were dissected into small pieces (approximately 1-2 mm wide) and all pieces were autotransplanted underneath the kidney capsules.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, autotransplantation of ovarian tissue has been demonstrated in mice. Our previous study demonstrated that fresh ovarian tissues that were autotransplanted underneath the kidney capsule supported pregnancy and full-term fetal development for transferred embryos [11]. We also demonstrated that vitrified-warmed ovarian tissue autotransplantation (VOAT) into estrus cycle-ceased ovariectomized mice restored fertility to achieve full-term fetal development for transferred embryos [12].…”
Section: Introductionmentioning
confidence: 93%
“…Vitrification of ovarian tissues and autotransplantation were performed as described previously with slight modifications [11,12]. Briefly, ovaries were dissected into small pieces (approximately 1-2 mm wide) and autotransplanted underneath the kidney capsules.…”
Section: Vitrification Of Ovarian Tissues and Autotransplantationmentioning
confidence: 99%